EFEKTIFITAS BERKUMUR DENGAN LARUTAN AIR PERASAN JERUK NIPIS (CITRUS AURANTIFOLIA) TERHADAP INDEKS PLAK PADA SISWA/I MTS NEGERI STABAT KEC. WAMPU KAB. LANGKAT SUMATERA UTARA - Asmawati ,; Ety Sofia Ramadhan; Adriana Hamsar; Renny Asnita (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLETHE POTENCY OF LIME WATER SOLUTION (CITRUS AURANTIFOLIA) AS MOUTHWASH TO PLAQUE INDEX OF STUDENTS IN MTS NEGERI STABAT, WAMPU, LANGKAT, NORTH SUMATERAABSTRACTPlaque which stuck on teeth provides nutrition for bacteria to grow and provide acid which will contact with tooth surface so that enamel dissolves and causes caries. Forestalling the growth of plaque can be done chemically. The research used the solution of lime crush (Citrus aurantifolia) as mouthwash which is able to impede the growth of plaque since it has various phytochemical compounds which has anti-bacteria that can decrease the number of bacteria forming plaque by denaturizing bacterium cell protein.The objective of the research was to find out influence of the solution of lime crush on the accumulation of plaque. Clinical test was conducted by using non-equivalent control group. The sample were 37 students of MTs Negeri, Stabat, Wampu Subdistrict, Langkat District; treatment group was given the solution of lime crush concentration of 25%, while the control group was asked to mouthwash with water.The result of the research showed there was the mean difference between the treatment group and the control group (p 0,05), plaque score in the treatment group (p=0.0001) was 1.73, while plaque score in the control group (p=0.0001) was 1.54. The conclusion of the research was the mouthwash with lime crush solution could descrease of accumulation of plaque.